2016
DOI: 10.15244/pjoes/61820
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Growth Promotion of Phosphate-Solubilizing Bacteria Associated with Nicotiana Tabacum (Tobacco)

Abstract: Phosphate-solubilizing bacteria (PSB) increase phosphate bioavailability, thereby reducing the application frequency of chemical fertilizers in the production of Nicotiana tabacum (tobacco). In this study, PSB were isolated from tobacco plants for the fi rst time. These PSB were screened in vitro for their ability to solubilize inorganic P (Pi) when grown in association with tobacco plants. Thirty-six PSB with the ability to solubilize P i were isolated and screened for their indolyl-3-acetic acid and sideroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…These results indicated that in the greenhouse and field environments, the PSB could improve the barren rocky soil fertility and promote sweetpotato growth. In adition, some PSB also showed a good growth-promoting effect on a variety of crops, such as O. haematophilum could promote the growth of corn and tobacco ( Pereira and Castro, 2014 ; Gao et al, 2016 ). It would be an interesting and valuable work to study the effect of these screened PSB, especially the FP12, on other crops in future.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that in the greenhouse and field environments, the PSB could improve the barren rocky soil fertility and promote sweetpotato growth. In adition, some PSB also showed a good growth-promoting effect on a variety of crops, such as O. haematophilum could promote the growth of corn and tobacco ( Pereira and Castro, 2014 ; Gao et al, 2016 ). It would be an interesting and valuable work to study the effect of these screened PSB, especially the FP12, on other crops in future.…”
Section: Discussionmentioning
confidence: 99%
“…Control was determined as medium without fungi inoculation. The pH of medium was measured to determine the effect of phosphate dissolution by fungi on the pH of medium (Gao et al 2016).…”
Section: Quantitative Testing On Pikovskaya Liquid Mediummentioning
confidence: 99%
“…Here, we report the first complete genome sequence of Ochrobactrum haematophilum , a Gram-negative, nonmotile, rod-shaped, oxidase-positive bacterium from the Alphaproteobacteria class. This species was first isolated from human blood ( 1 ) but is frequently associated with plants ( 2 ) and the rhizosphere ( 3 , 4 ). O. haematophilum has been reported to promote plant growth through the solubilization of phosphates and the production of siderophores ( 3 , 4 ) and to produce fungicidal substances ( 4 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Among them are the gene cluster efeUOB, putatively encoding an elemental ferrous iron transporter ( 11 ), the fepC , fepG, fepD , and fepB genes, putatively encoding a ferric enterobactin transport system, a gene cluster putatively encoding the vitamin B 12 transport system BtuCDF ( 12 ), and several genes putatively encoding TonB-dependent transporters, which bind and transport ferric chelates, as well as vitamin B 12 , nickel complexes, and carbohydrates ( 13 ). The capacity of this microorganism to chelate iron can promote plant growth ( 3 , 4 ); however, it could be detrimental to the nutritional value of the fermented foods from which it was isolated. The presence of two genes encoding putative exopolyphosphatases could be related to the phosphate solubilization activity described for this species ( 2 , 4 ).…”
Section: Genome Announcementmentioning
confidence: 99%